Membangun Karakter Peduli Sosial Melalui Sedekah: Integrasi Nilai Islam dan Sains dalam Pendidikan - Muharrani; Risnawati; Edi Yusrianto; Safdar Bhatti, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This research raises the importance of integrating Islamic values, especially almsgiving, with a scientific approach in forming socially caring character. The phenomenon of a lack of empathy and social concern, especially among students, prompted this research to explore the concept of alms as a learning instrument that not only strengthens spiritual values, but also provides psychological and social benefits. The aim of this research is to describe the role of alms in building socially caring character and examine the relevance of integrating Islamic values ​​and science in character education. This research uses a literature review method, by analyzing articles from various sources that discuss alms, Islamic religious education, social care character education, integration of Islamic values ​​and science. The analysis process is carried out through selection of inclusion and exclusion criteria to ensure data validity. The research results show that almsgiving has a significant impact in increasing empathy, strengthening social relationships, and building deep social awareness. From a scientific perspective, the act of giving improves psychological well-being and reduces stress, while from an Islamic perspective, almsgiving is a form of worship that strengthens the spiritual connection with Allah SWT and social solidarity in society. The contribution of this research is to provide a conceptual basis for integrating Islamic values ​​and science in the educational curriculum, especially in the formation of socially caring character. This research encourages the development of holistic and contextual learning strategies, making alms an effective approach in forming an empathetic and socially responsible young generation.